PENINGKATAN PERANCANGAN SISTEM INFORMASI MERCHANDISE INSIDE LOMBOK BERBASIS WEBSITE MENGGUNAKAN API WHATSAPP - Habib Ratu Perwira Negara; Ahmad Ahmad; I Komang Wira Aditya (LPPM Universitas Bina Bangsa, 2021)
Aims to be able to help PT. Lombok Media Utama (Inside Lombok) in managing all its merchandise catalogs on the website and making it easier for customers who want to buy merchandise to input the purchase format using the WhatsApp API. This activity is in the form of making a website using the prototyping method and training carried out by the team by providing training to the Inside Lombok admin staff in the form of directions on the flow of using this website application, the participants involved are the inside Lombok admin staff. From the results obtained after testing using BlackBox Testing and evaluation of satisfaction, quite satisfactory results were obtained where the admin managed to manage merchandise products easily, and customers could also use the features on the website smoothly to fill in the format with the Whatsapp API feature to be more efficient